Existence of Backward Bifurcation and Global Analysis of Imbalanced System: Pollutants -- Rain -- Toxicity - Shah, Nita H.; Satia, Moksha H.; Suthar, Ankush H. (Journal of Applied Nonlinear Dynamics, 2026)
Anthropogenic activity along with natural activity has increased the level of pollutants into the atmosphere. The amount of pollutants has replaced the clean air molecules with the toxic air pollutants. This impacts the average rain fall negatively. Moreover, natural rain fall is one of the remedies to reduce toxicity. Toxicity in turn creates pollution. This cycle of pollutants, rain and toxicity is studies through the formulation of system of non-linear differential equations. Threshold for pollutants is performed to monitor the effect on rain and toxicity. To maintain threshold under control, backward bifurcation is workout. The results derived in the proposed model are supported by numerical simulation.